Volatility Spillover and Co-Movement between Oil Price Shocks and the Nigerian Equity Market Returns - Paul Ndubuisi (Archives of Current Research International, 2017)
This study investigates empirically the volatility spillover and co-movement between oil price shocks and equity return behavior in Nigeria. Data for the study were obtained from secondary sources particularly from Central Bank of Nigeria (CBN) and Nigeria Stock Exchange Publications. Data covered the period 2000 to 2015 and were analyzed using Exponential Generalized Autoregressive conditional Heteroscedasticity (EGARCH) model for the volatility spillover and Autoregressive Distributive Lag (ARDL) model for long and short dynamics. The results are three folds: First, the results revealed that oil price volatility has a significant negative impact on stock returns in Nigeria. Second, the results also revealed that there were leverage and symmetric effects and volatility persistence in the Nigeria Stock Market. Third, the study confirms co-movement between oil price shock and equity returns in Nigeria. The study therefore recommends that the government should carefully monitor developments in the world crude oil market with a view to diversifying the economy away from crude oil dependence to minimize the consequences of oil shocks on the stock market and the economy at large.